Validation and utilisation of a digital version of the survey instrument for natural history, Aetiology and Prevalence of Patellofemoral pain studies (eSNAPPS). (July 2021) - Yusuf, Mohamed; Dey, Paola; Callaghan, Michael; Relph, Nicola; Gichuru, Phillip; Pinner, Susan; Ashbrook, Jane; Ashman, Joanne; Goodwin, Peter; Macdonald, Ruth; Selfe, James
Abstract: Objective: This study validated the newly adapted electronic SNAPPS (eSNAPPS) against the original paper SNAPPS. Subsequently, the study estimated the prevalence of PFP in running participants and spectators attending three mass-participant running events in the United Kingdom by using the eSNAPPS tool. Design: This study had two parts. Firstly, a validation of the original paper version of the SNAPPS tool. Secondly, if validation was achieved, eSNAPPS was used in a prevalence study. Participants: A convenience sample of running participants and spectators aged 18–40 years attending the mass participation running events. Main outcome measure: The 12-month prevalence of PFP. Results: eSNAPPS was valid in identifying those with PFP (ICC 0.99 for Overall agreement, p < 0.0001). In the prevalence study, a total of 1080 running participants and spectators completed the eSNAPPS. The overall prevalence of PFP was 17.4% (95%CI: 15.2%, 19.8%); 20.5% of males (16.5, 24.9) and 15.7% of females (13.1, 18.7) had PFP. Prevalence was 17.4% (15.2, 19.8) in spectators and 16.7% in running participants (14.5, 19.0). Conclusion: The overall PFP prevalence in this study was slightly smaller than those previously reported in the literature. Findings also show that there were similar prevalence estimates in spectators and running participants. Highlights: What are the new findings? 1 The agreement between digital and paper SNAPPS was high, therefore suitable for use in population-based setting to determine the prevalence of PFP. 2 In spectators and runners attending a mass-participant running events, overall, 12-month PFP prevalence was 17.4%. It was higher in runners than in spectators (19.3% in spectators and 16.4% in runners). 3 Patellofemoral pain was most prevalent in those aged 31–35 years and was more prevalent in males than females 20.5% males, 15.7% in females). 4 The care-seeking behaviour of those with PFP is similar to that of individuals with 'other knee problems', as 47% of those who presented specifically with PFP had previously consulted a doctor about their knee problems, and 54% of those of those with other knee problems had consulted a doctor about a knee problem.